Photon-Counting CT in the Head and Neck: Current Applications and Future Prospects - Benson, John C.; Campeau, Norbert G.; Diehn, Felix E.; Lane, John I.; Leng, Shuai; Moonis, Gul (American Journal of Neuroradiology, 2024)
Photon-counting detectors (PCDs) represent a major milestone in the evolution of CT imaging. CT scanners using PCD systems have already been shown to generate images with substantially greater spatial resolution, superior iodine contrast-to-noise ratio, and reduced artifact compared with conventional energy-integrating detector–based systems. These benefits can be achieved with considerably decreased radiation dose. Recent studies have focused on the advantages of PCD-CT scanners in numerous anatomic regions, particularly the coronary and cerebral vasculature, pulmonary structures, and musculoskeletal imaging. However, PCD-CT imaging is also anticipated to be a major advantage for head and neck imaging. In this paper, we review current clinical applications of PCD-CT in head and neck imaging, with a focus on the temporal bone, facial bones, and paranasal sinuses; minor arterial vasculature; and the spectral capabilities of PCD systems.CIcochlear implantCNRcontrast-to-noise ratioEIDenergy-integrating detectorPCDphoton-counting detectorSSCDsuperior semicircular canal dehiscenceVMEvirtual monoenergetic